The effects of an exogenously-induced ketosis on human exercise physiology, metabolism and capacity - Dearlove, D (2021)
Ketosis is a pivotal metabolic adaptation to starvation that prolongs survival by altering fuel utilisation. If harnessed outside the context of starvation, ketosis may provide a method to enhance physical performance. Therefore, this Thesis explored the effects of an exogenously-induced ketosis on human exercise physiology, metabolism and capacity. First, how the mild-ketoacidaemia associated with ketone supplementation affects the physiological response to incremental-intensity exercise and athletes’ perceptions of exercise exertion were determined (Chapter 3). To compensate for ketoacidaemia, exercise ventilation was increased by 5% and exercise-induced hyperventilation was at a 20 W lower intensity. Perceptions of exertion were greater during ketosis, primarily due to the increased acid load. Chapter 4 determined the effects of blood β-hydroxybutyrate (βHB) concentration and exercise intensity on βHB oxidation rates. Increasing blood βHB concentration from ≈2 mM to ≈4.5 mM did not affect βHB oxidation rates. βHB oxidation rates peaked during 50% maximal power (WMax) intensity exercise, although the greatest relative contribution to overall energy expenditure was during 25% WMax intensity exercise and just 4.5%. Despite this, delta efficiency was increased during ketosis. Finally, in Chapter 5, the effects of prolonged exogenously- and endogenously-induced ketoses on exercise capacity and adaptive responses to exercise training were compared. Ketone supplementation improved exercise capacity by 4 - 6% on 50% of training days versus a carbohydrate (CHO) control, but markedly impaired whole-body insulin sensitivity. Conversely, a ketogenic diet substantially increased fat oxidation by ≈60% during exercise. In part, this was caused by changes in skeletal muscle protein content, most notably a 5-fold increase in pyruvate dehydrogenase kinase 4. However, exercise capacity was decreased by 41 - 48%. In conclusion, despite increased awareness of exercise exertion, and low βHB oxidation rates, supplementing athletes with ketones may enhance exercise efficiency and capacity in athletes. However, prolonged supplementation during exercise training may result in unfavourable metabolic adaptations to CHO metabolism, without reciprocal increases in fat metabolism, as observed with an endogenously-induced ketosis.